Development of control system of automated guided vehicle - Abu Harfiz, Hassan (2009)
The thesis focuses on the development of control system for automated guide vehicle. The development is referring either develop something new or based on existed on earth. To achieve that, we go to basic concepts of how controlling the microcontroller. It is important to know the features of microcontroller, and what suitable port to used. This development was carried out by doing some fabrication of AGV and programs it using C language. Another additional innovative for improving the control system of AGV is sensor. Research concentrates on type of sensor. It is determining their function, whether line follower AGV or light follower. The AGV can be commercialized and replace human work.